Construction and Pilot Test of an Instrument to Measure the Gaps in Teaching-Learning of Science at Middle Stage in Select Tribal Dominated Rural Schools of Chhattisgarh, India - Khatri, B. K. Tripathi; Bhaduri, Indrani; Garg, Rachna; Srivastava, Ashish Kumar; Kumar, Dinesh; Parashar, R K; Verma, Ruchi; Farkya, Sunita (SCHOOL SCIENCE, 2017)
The present study intends to develop tools to find out the gaps in science teaching and learning in select schools of scheduled tribes-dominated districts of Chhattisgarh. The tools development was completed in four phases following a modified Plomp model. In the preliminary investigation phase, research team members visited the schools of Chhattisgarh to analyse and determine the need. In the design phase, with the help of experts' opinion, the design of tools was finalised. In the construction phase, the development of four tools and their review with the panel of experts was carried out. These tools were; Tools for assessing attainment to leaner in leaning science for Classes VI, VII and VIII (TALS); a tool for attitude of learners in learning science (TATLS), Classroom Observation Schedule (COS), School Observation Schedule (SOS). Draft tool for Performance Indicators for Teachers (TPIT) developed by NCERT was administered in the study with minor modifications. In the time final, test evaluation and revision phase four, after the pilot test of tools in four schools of Raipur, Chhattisgarh, and data analysis, four tools were finalised again by a panel of experts. However, for the tool for assessing learners' attainment in learning science (TALS) for Classes VI, VII and VIII after applying in SPSS version 16 and Kuder Richardson formula 20, (KR 20), individual item analysis was suggested in the study